Pengetahuan Ibu Hamil Tentang Tanda Kegawatdaruratan Kehamilan Dengan Kepatuhan Dalam Pemeriksaan Antenatal Care di Wilayah Kerja Puskesmas Glagah - Yusri Dwi Lestari; Sulis Winarsih (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Emergencies in pregnancy need to be detected early to find out pregnant women who may experience complications in their pregnancy so that treatment can be done immediately. Knowledge of pregnant women about emergency signs of pregnancy can affect the attitudes and behavior of pregnant women about their pregnancy care. The purpose of the study was to determine the relationship between knowledge of pregnant women about emergency signs of pregnancy and compliance in antenatal care examinations. In this study using a correlational design with a cross sectional approach. With a sample of 30 respondents with accidental sampling technique. Data was collected by filling out a closed questionnaire, the results of the questionnaire were tabulated and data analysis was carried out. The results of the Chi Square test of the relationship between knowledge of pregnant women about emergency signs of pregnancy and compliance with antenatal care examinations obtained p-value = 0.002 and p-value is less than 0.05 or 0.002 <0.05, it is concluded that there is a relationship between knowledge of pregnant women about signs signs of emergency pregnancy with antenatal care examination compliance. Thus, pregnant women who obediently perform antenatal care have good knowledge about emergency signs of pregnancy.